Pengaruh Metode Focus Group Discussion Terhadap Antusias Belajar Siswa pada Mata Pelajaran PAI di SMPN 1 Sungai Pua - Gusnia Darniati; Hamdi Abdul Karim; Mustafa Mustafa; Ulva Rahmi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to determine the effect of using the focus group discussion method on students' enthusiasm for learning in the Islamic religious education subject class VIII SMPN 1 Sungai Pua. This research uses a quasi-experimental research method by taking two classes which are used as a control class and an experimental class. This research is a quantitative experiment, by giving pre-tests and post-tests to students in both classes. Totaling 50 people. The sampling technique was carried out using Cluster random sampling technique. The instrument used for data collection was a learning interest questionnaire. The data analysis technique uses normality, homogeneity tests, then continues with hypothesis testing. From the research results, it shows that the results of hypothesis testing that was carried out in the experimental class and control class obtained a Sig value. (Pvalue) = 0.001˂ α = 0.05. which means H0 is rejected and Ha is accepted. Based on the results of these calculations, it can be concluded that there is an influence of using the focus group discussion method on students' enthusiasm/interest in learning in class VIII Islamic Religious Education subjects at SMPN 1 Sungai Pua.